Uma proposta de formação continuada para professores de língua portuguesa a partir da produção de textos multimodais - Silva Júnior, Eurico Rosa da (2022)
This study investigates the training of Portuguese-speaking teachers in the final years of elementary school in the municipality of São José do Egito-PE in relation to the production of multimodal texts as provided for in the National Common Curricular Base - BNCC (BRASIL, 2017). The research has as general objective: to investigate whether the continuing education offered by the municipality of São José do Egito-PE meet the BNCC assumptions regarding the production of multimodal texts in the final years of elementary school and the following specific objectives: a) to analyze the training of Portuguese language teachers in the final years of elementary school in São José do Egito-PE regarding multimodal texts; b) discuss the contributions of continuing education to the work of Portuguese-speaking teachers in the final years of elementary school in São José do Egito-PE; c) offer a continuing education course for Portuguese speaking teachers in the municipality of São José do Egito-PE regarding multimodal textual production; d) highlight the relevance of the production of multimodal texts in the classroom practice of the Portuguese language teacher; e) present the contributions brought by the BNCC on the production of multimodal texts; f) reflect on the strategies (or lack thereof) used by Portuguese language teachers in the final years of elementary school in São José do Egito-PE to appropriate multimodal texts and work with them in their teaching practice; and g) contribute to the awareness of managers about the importance of continuing education courses for teachers of basic education in the final years of elementary school. It is a qualitative and exploratory research with a qualitative-interpretative approach. As a theoretical basis, we bring the discussions on the pedagogy of multiliteracies and multimodality present in Ribeiro (2020), Hissa e Sousa (2020), Fischer (2007), Raulik (2017), Rojo and Barbosa (2015) and Brasil (2017) ; As contributions to teacher training and the use of digital tools in education, we bring the postulates of Veiga (2008), Leitão de Melo (1999), Imbernón (2016), Ferrarezi Júnior (2014), Brazil (1996 and 2020), PESSOA ( 1986), Guedes (2006), Xavier (2013), Guedes and Viana Júnior (2013), ARAÚJO (2014), Roza and Menezes (2019); To discuss the relevance of textual genres in the classroom and their production, we use the postulates of Brasil (2017), Ribeiro (2016 and 2020), Santos, E. (2019), Ferrarezi Júnior and Carvalho (2015), Marcuschi ( 2008), Porto (2009), Matos and Azevedo (2019), Passarelli (2012), Silva and Luna (2012), Antunes (2009) and Munhoz and Abreu (2019). To achieve the objectives of this research, were used as methodological procedures, at first, bibliographic research, documental survey and application of structured questionnaires with Portuguese language teachers of the final years of elementary school in the mentioned municipality. Preliminary results highlighted the difficulties faced by teachers regarding the use of multimodal texts and their effective production in the classroom. Based on the data collection from the questionnaire, a 120-hour course was developed for the teachers participating in the research, with a view to improving the quality of teacher training and improving the practice related to the production of multimodal texts. In this second moment, the methodology of action research was used. The course achieved our intended objectives for this action, considering that the notes of the teachers make it clear that the discussions held during the course were profitable and fruitful for the day to day of the classroom and that the proposals launched there are relevant to the classroom use. In summary, based on the teachers' notes and our analyses, it is also evident that much needs to be done with regard to teacher training, with regard to multimodal textual production, as well as in relation to the awareness of teachers for decision making. regarding the importance of effective participation in continuing education courses offered by the most diverse institutions.